Long-term impacts of environmental policy and eco-innovative activities of firms - Klaus Rennings; Sascha Rexhäuser (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
This paper analyses two aspects of environmental regulations triggered by ecoinnovations. First, whether there are long term effects of regulation on innovation. Second, whether the impact of different types of regulation differ by type of the environmental benefit of the innovations. To answer these questions, the paper uses firm level data from the German part of the Community Innovation Survey 2009, in which companies were asked to cite the respective regulations to be responsive for the firms' introduced environmental related innovations. Regulations quoted by firms are classified into several policy types and also the age the respective regulations are calculated. We find evidence for long-term effects of environmental regulation on innovation. Furthermore, different types of regulations varied with respect to their impact on several environmental benefits of innovations.
Keywords: Q55; Q58; Q01; C83; 330; environmental policy; environmental innovation; innovation surveys; Umweltpolitik; Umweltauflage; Wirkungsanalyse; Umweltschutz; Innovation; Ökonomischer Anreiz; Nachhaltigkeit; Schätzung; Deutschland